Tradisi Seblang Olehsari; Makna Simbolik Ritual Bersih Desa Olehsari Sebagai Budaya Lokal Banyuwangi - Anastasya Gawal Putri; Fiky Binti Zakiyah; Yolanda Naomi Martdina (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
At this time, times are increasingly developing and experiencing rapid progress, so that the term "modernity" appears. Currently, what is really feared is "the methods or actions that need to be taken by young people in maintaining the values ​​or meaning contained in the seblang tradition" if you look at the increasingly advanced way of thinking and behavior of young people today. The seblang tradition originates from Banyuwangi, East Java, Olehsari Village, whose cultural community still upholds customs and social harmony. The seblang tradition is a dance performed to ward off evil or bad luck which is performed once a year, precisely on holidays. The method used in the research is qualitative research, namely using ethnography which explains the norms, traditions, values ​​and actions carried out in the Seblang dance. The seblang tradition has been passed down from generation to generation and is mandatory. If this tradition is not carried out within a year, one of the ancestral spirits will come to one of the residents and possess the resident to give a "sign" that the seblang haru tradition is being carried out. Apart from that, the existence of modernity poses a risk if it is forced into seblang traditions. Because the risk posed will dilute the meaning contained in the seblang tradition.